Empowering the Youth Community in Building a Literacy Village in Tegalsari, Kandeman, Batang: Pemberdayaan Komunitas Pemuda dalam Membangun Kampung Literasi di Desa Tegalsari, Kandeman, Batang - Mukhlis, Abdul; Alghiffary, Muhammad; Al-Bajilah, Salman; Ulzima Stari, Tamaro (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Reading and literacy activities are often carried out by school institutions. In fact, reading and literacy are basic competencies that a person must have in order to survive in life. Meanwhile, reading learning and literacy activities in class do not yet have a sufficient portion to be able to provide comprehensive provisions to students. This community service activity is carried out to strengthen reading and literacy skills in the general public outside school institutions. Apart from that, this activity also aims to encourage the young generation in Tegalsari Village, Kandeman District, Batang Regency to have critical awareness in all their activities, especially in the field of education. Therefore, this service uses Participatory Action Research (PAR) as an approach method with the hope of creating social transformation carried out by the fostered partners or the youth community itself. Through PAR, this service produces three recommendations in the form of a flow of activities as the expected final achievements, namely planning, implementation and evaluation. Based on these results, the service team, youth community, community and village government discovered how important the existence of reading huts is in busy nodes or places of community activity. Through this literacy village pilot, the youth community and the people of Tegalsari Village gained a new perspective that the literacy village pilot became a symbol of progress and stability in the village community's thinking